Qibla Direction Determination: A Systematic Literature Review on The Role of Mathematics in Islamic Education - Azzahra, Salsabila; Kariadinata, Rahayu; Rachmawati, Tika Karlina (IKIP Siliwangi, 2025)
Accurate Qibla direction is a fundamental aspect of Muslim worship, especially in prayer. However, many studies have reported significant inaccuracies in Qibla determination, particularly in areas lacking proper astronomical tools or knowledge. At the same time, interest in mathematics among students in Islamic education remains relatively low, despite its critical role in religious practices. This study aims to systematically review recent literature that explores the role of mathematics in Qibla direction determination and its integration into Islamic education. A Systematic Literature Review (SLR) was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Fourteen articles published between 2020 and 2024 were selected from indexed journal databases based on specific inclusion and exclusion criteria. Data collection involved document analysis of journal articles, books, and theses using relevant keywords such as “Qibla direction,” “Islamic education,” and “mathematics.” The selected articles were analyzed thematically and categorized based on year of publication, mathematical concepts applied (e.g., spherical trigonometry), and educational integration. The results show that mathematical approaches particularly spherical trigonometry play a central role in achieving high accuracy in Qibla direction determination. Furthermore, the integration of these mathematical concepts into Islamic education enhances students’ understanding of the connection between science and religion. This review suggests that embedding mathematical applications into Islamic contexts can increase student motivation and strengthen the relevance of mathematics in daily worship.